Transferring an extremely premature infant to an extra-uterine life support system: a prospective view on the obstetric procedure - van Haren, Juliette S.; Delbressine, Frank L. M.; Schoberer, Mark; te Pas, Arjan B.; van Laar, Judith O. E. H.; Oei, S. Guid; van der Hout-van der Jagt, M. Beatrijs (Frontiers in Pediatrics, 2024)
To improve care for extremely premature infants, the development of an extrauterine environment for newborn development is being researched, known as Artificial Placenta and Artificial Womb (APAW) technology. APAW facilitates extended development in a liquid-filled incubator with oxygen and nutrient supply through an oxygenator connected to the umbilical vessels. This setup is intended to provide the optimal environment for further development, allowing further lung maturation by delaying gas exposure to oxygen. This innovative treatment necessitates interventions in obstetric procedures to transfer an infant from the native to an artificial womb, while preventing fetal-to-neonatal transition. In this narrative review we analyze relevant fetal physiology literature, provide an overview of insights from APAW studies, and identify considerations for the obstetric procedure from the native uterus to an APAW system. Lastly, this review provides suggestions to improve sterility, fetal and maternal well-being, and the prevention of neonatal transition.